New species of Benthana Budde-Lund, 1908 (Crustacea: Oniscidea: Philosciidae) from Paraná, Brazil - Campos-Filho, Ivanklin S.; Araujo, Paula Beatriz (Zootaxa, 2011)
The Neotropical genus Benthana Budde-Lund, 1908 includes 22 species, three of them allocated to the subgenus Benthanoscia Lemos de Castro, 1958. A new species is described from the state of Paraná, Brazil. This new species is distinguished from its congeners by having 8+2 aesthetascs on the antennula, the first article of the antennal flagellum unpigmented, the proximal inner tooth of the inner pectinate set of the maxillula with 7 denticles, and the pleopod 1 exopod with a dentiform protrusion with a concave appearance.